2016
DOI: 10.1134/s1075700716060113
|View full text |Cite
|
Sign up to set email alerts
|

Social entrepreneurship in the system of social policy: International experience and prospects of Russia

Abstract: ⎯The article deals with a relatively new phenomenon for Russia, i.e., social entrepreneurship. Based on an analysis of international experience in the development of social enterprises, their characteristics have been studied, the advantages and risks in support of social enterprise in meeting the social needs have been revealed, and the problems and prospects of development of social entrepreneurship in Russia have been discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Therefore, social entrepreneurs can be defined as change agents that employ entrepreneurial means to find systemic solutions to social and environmental problems [24]. They must have a clear and specific social goal that prioritizes social value creation [8], although the initiative of social entrepreneurship can come both from the business sector (business approach motivated by a mission) and nonprofit organizations (earned income school of thought) [25]. Thus, this type of entrepreneurship can comprise a rather broad range of organizations, such as (1) traditional nonprofit organizations, which have a clear social mission and which are not dependent on market income (the commercial activities undertaken in this type of business can produce profits that will enable the business to maintain its operations), (2) for-profit organizations that have a clear mission to seek both social and economic objectives, and (3) hybrid organizations whose motives are both not-for-profit and for-profit.…”
Section: Literature Background and Development Of Hypothesesmentioning
confidence: 99%
“…Therefore, social entrepreneurs can be defined as change agents that employ entrepreneurial means to find systemic solutions to social and environmental problems [24]. They must have a clear and specific social goal that prioritizes social value creation [8], although the initiative of social entrepreneurship can come both from the business sector (business approach motivated by a mission) and nonprofit organizations (earned income school of thought) [25]. Thus, this type of entrepreneurship can comprise a rather broad range of organizations, such as (1) traditional nonprofit organizations, which have a clear social mission and which are not dependent on market income (the commercial activities undertaken in this type of business can produce profits that will enable the business to maintain its operations), (2) for-profit organizations that have a clear mission to seek both social and economic objectives, and (3) hybrid organizations whose motives are both not-for-profit and for-profit.…”
Section: Literature Background and Development Of Hypothesesmentioning
confidence: 99%
“…At times of global financial crisis starting from 2008, nearly all single-industry towns had a different set of problems the main of which was a sharp decline in investment activity, the temporary suspension of investment projects, and from time to time the refusal to implement them. Antirecessionary measures aimed to improve the situation were to reduce spending on social programs and personnel, to discharge employees, so they caused drastic consequences for the people [15].…”
Section: Discussionmentioning
confidence: 99%
“…Because cases for the analysis were sampled from participants of capacity-building events for SONPOs in the process of developing for-profit activities, we were not able to access well-established social enterprises and cannot contribute to the debate about differences and similarities between these types of organizations (Moskovskaya et al 2017;Moskovskaya and Soboleva 2016). Earlier research on hybridity demonstrated that business logic eventually prevails when it contests the nonprofit logic, although they intertwine to create a continuous spectrum of values and activities rather than a binary opposition (Zhang and Swanson 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Alongside small and medium-size social businesses, they are targeted by state centers for social sphere innovations which, since 2012, have spent 1.5 billion RUB on entrepreneurial social initiatives (Nikolaeva 2017). Because social entrepreneurship still lacks a clear legal definition (Moskovskaya et al 2017;Moskovskaya and Soboleva 2016), nonprofits often need to identify with or distinguish themselves from the practice of social entrepreneurship (Chuprova 2014), and bear the associated costs and risks. In this article, we attempt to answer following questions: How do Russian SONPOs balance market demands with statutory goals when introducing for-profit activities?…”
Section: Introductionmentioning
confidence: 99%